A comparative study on the quality attributes, phenolic content and antioxidant activity of cultivated and wild asparagus as influenced by seasonal variations. (12th December 2022) - Alan, O.; Turk, B.; Sen, F.
Abstract: The wild asparagus Asparagus acutifolius L. is common in the Mediterranean Basin. Wild asparagus spears are an important food source within their native range, and can be used as a sustainable nutrition source. In addition, interest has risen in wild relative species of Asparagus as a source of genetic improvement in Asparagus officinalis L. In this study, the quality traits (spear colour, total soluble solid content, dry matter content and chlorophyll and sugar fractions) and health-related compounds (total phenolics and antioxidant capacity) of fresh spears of wild and cultivated asparagus grown in Turkey were compared using the same three harvest periods for two consecutive years. The results of this study indicated that spears of wild asparagus contained a higher level of greenness (– a *), hue angle, total soluble solid, dry matter, chlorophyll, sugars, total phenolic content and antioxidant activity, compared to cultivated asparagus. Although there was no significant difference in the total soluble solid, glucose, sucrose and antioxidant activity in the contents of the spears of both species throughout the season, the colour, dry matter, chlorophyll, fructose, total sugar and total phenolic content were subject to seasonal variations. Colour, chlorophyll and total phenolic content showed some minor fluctuations over the course of the season, but the patterns of fructose and total sugar differed, which tended to increase throughout the harvest season. The present work suggests greater quality traits and biochemical compounds of the spears of A. acutifolius compared with those of commonly cultivated species.